Чехов в жизни: сюжеты для небольшого романа / И. Н. Сухих - Сухих Игорь Николаевич (Диалог, 2011)
Экземпляры: СФ-8 (20120720) / Инвентарный номер: 40902z8 / Цена: 205.6 / Сис.шифр: 83.3(2Р) / Авт.знак: С 91 / ГРНТИ: 17.09.91 / ББК: 83.3(2Рос=Рус)